Evaluating Key Risk Factors for Tuberculosis: Insights from a 2019-2024 Literature Review - Ashila, Naura Rahma; Nurwahidah (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify the risk factors for Tuberculosis (TB) through a comprehensive literature review. Understanding these risk factors is essential for effectively preventing and managing TB. Methods: The study employed a literature review method, which is beneficial for obtaining relevant research and synthesizing previous findings. Data sources included national and international journals on TB risk factors obtained from Google Scholar, covering publications from 2019 to 2024. The data analysis involved identifying the research design, study location, publication year, sample size, and number of variables examined. Results: The analysis provided an overview of studies on TB risk factors, including 10 studies conducted domestically and internationally from 2019 to 2024, with the highest number of studies published in 2020. The identified risk factors for TB include age > 75 years, male gender, low knowledge levels, unemployment, history of TB contact, active smoking, low education levels, and living in poorly ventilated houses. Conclusion: The study concludes that several risk factors contribute to the incidence of TB, such as advanced age, male gender, low socioeconomic status, and poor living conditions. Recommendations include encouraging individuals living in poorly ventilated homes to adopt Clean and Healthy Living Behaviors (PHBS) by improving ventilation to allow sunlight and air exchange. Additionally, there is a need for increased public access to TB-related information to enhance knowledge. Governmental efforts are crucial in implementing TB prevention programs, educating on proper cough and sneeze etiquette, and enhancing early detection to break the transmission chain.